Improving fertility in Holstein friesian herd by single dose prostaglandin injection through vulvovaginal submucosal route - MOHANTY, L D; MISHRA, P C; PRADHAN, S (The Indian Journal of Animal Reproduction, 2023)
Single injection of prostaglandin F, (0 . 0 ➔ 5 mg clorrostenol) was tried in a HF herd through vulvo-vaginal submucosal route for oestrus synchronisation , here ocstr s detection and insemination posed a lot of difficulties as the animals were reared below the optimal manage111ental conditions. The ani111als possessing a good palpable C.L were grouped into 3 groups viz. Heifer. Milch & Dry. All the groups responded in a co111parabk 111anner and yielded an overall conception rate of 60%. when AL was done at 72 and 96 hrs . of PG administration.